Revitalizing Divorce Ethical Values in Verstek Decisions in Religious Courts/Revitalisasi Nilai Etika Perceraian dalam Putusan Verstek Di Pengadilan Agama - Izzuddin, Ahmad; Rofiq, Ahmad; Hapsin, Abu (De Jure: Jurnal Hukum dan Syari'ah, 2021)
AbstractDivorce is still a social problem in Indonesia. Divorce must be done in court. Ironically, most divorce cases are decided verstek because the defendants are not present in court. One of the courts that deal with divorce cases is the Malang Religious Court. This article is doctrinal legal research with a conceptual approach and a case approach. The primary data source is the divorce decision in the Malang religious court. The results of this study indicate that the verstek decision in the religious court should not be a gap for husbands to escape responsibility for their wives and children after divorce. The panel of judges also needs to use ethical values in divorce such as the principles of ma'rf, islâh, ihsân and afw in giving verstek decisions. It is necessary to revitalize the ethical values of divorce in the Verstek decision in the Religious CourtsKeywords: divorce; religious court; verstek.AbstrakPerceraian masih menjadi problem sosial masyarakat di Indonesia. Perceraian harus dilakukan di pengadilan. Ironisnya, sebagian besar perkara perceraian di putus secara verstek karena pihak tergugat tidak hadir di pengadilan. Salah satu pengadilan yang banyak menangani perkara perceraian adalah Pengadilan agama Malang. Artikel ini merupakan penelitian hukum doktrinal dengan pendekatan konseptual dan pendekatan kasus. Sumber data primer adalah putusan perceraian di pengadilan agama Malang. Hasil penelitian ini menunjukkan bahwa putusan verstek di pengadilan agama tidak boleh menjadi celah bagi suami untuk lepas tanggung jawab terhadap istri dan anak-anak pasca perceraian. Majelis hakim juga perlu menggunakan nilai-nilai etis dalam perceraian seperti prinsip ma’rûf, islâh, ihsân dan afw dalam memberikan putusan verstek. Sehingga perlu dilakukan revitalisasi nilai-nilai etika perceraian dalam putusan verstek di Pengadilan AgamaKata Kunci: perceraian; pengadilan agama; verstek